Education Policies and Practices for Ensuring Quality Education in Nepal - Acharya, Bisna (Nepal Journal of Multidisciplinary Research, 2024)
Background: Nepal's education policies and practices focus on enhancing the quality of education by implementing guidelines, regulations, and initiatives established by the government and educational institutions. The policies and practices are carefully crafted to address various aspects of the education system, ensuring that all students can access equitable, thorough, and effective educational opportunities. Objectives: This study examines the education policies and practices implemented in Nepal to ensure high-quality education. Method: An analytical and descriptive research design has been applied to analyze the data. Data were collected through a comprehensive field survey. Questionnaires were distributed to students, teachers, and guardians, while head teachers were interviewed. Additionally, policy experts and local leaders participated in a focused group discussion. Results: The study found a strong correlation between various dimensions of quality education and the overall quality of education. Specifically, motivation, teaching-learning pedagogy, school environment, and training and development were found to be statistically significant in improving the quality of education. However, no significant relationship was found between resources and the quality of education. The regression results also showed similar findings. Conclusion: Based on the hypothesis, it can be inferred that there was a positive impact of motivation, teaching-learning pedagogy, school environment, and training and development on the quality of education, even in primary and basic education settings. The study suggests that resources do not have a significant impact on the quality of education in primary and basic education. Novelty: The researcher has expected that by implementing education acts, policies, and programs, Nepal's school education will be improved ensuring education quality.